Application of five-element music therapy in pain coping skills training in patients with knee osteoarthritis - Suqian Li; Jingjin Xu; Ling Tang; Ye Li; Huaxin Wang; Lixue Zhao; Jianshuang Yao; Shuying Wang; Nan Li (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of this study is to assess the application effect of five elements music therapy introduced in the pain coping skills training of knee osteoarthritis (KOA). Materials and Methods: Totally, 80 patients with KOA were selected and randomly divided into the experimental group (39 cases) and the control group (41 cases). The control group was only given routine nursing measures, and the experimental group was additionally treated with five-element music therapy on the basis of the control group, twice a day, 28 days in total. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to evaluate the functional status of the knee joint of the two groups. The clinical efficacy of the two groups was evaluated by Guiding Principles for Clinical Research of New Chinese Medicine in the Treatment of Osteoarthritis. Results: WOMAC score statistically significantly decreased in the experimental group (35.92 ± 9.48 vs. 16.17 ± 5.43, P < 0.01) and the control group (36.73 ± 6.42 vs. 22.53 ± 7.51, P < 0.01) after 28 days of intervention when compared with that before intervention; WOMAC score in the experimental group was lower than that of the control group after 28 days of intervention (16.17 ± 5.43 vs. 22.53 ± 7.51, P < 0.01). The total effective rate of the experimental group was statistically higher than that of the control group (82.0% vs. 51.2%, χ2 = 11.97, P= 0.003). Conclusion: The combination of five-element music therapy and routine nursing measures has better effect in relieving pain and bad emotions of patients with KOA when compared with routine nursing measures alone.